ANALISIS KREATIVITAS GURU DALAM MODIFIKASI LAGU BERTEMA DI UPT SPF TK NEGERI SATU ATAP 01 LUBUK PAKAM - Katarina Herdinawati Lumban Gaol; May Sari Lubis (STKIP Subang, 2026)
This study was conducted in response to the need for teacher creativity in modifying theme-based songs to create meaningful and enjoyable learning experiences for young children. The objective of this study was to analyze teachers’ creativity in theme-based song modification at UPT SPF TK Negeri Satu Atap 01 Lubuk Pakam. This research employed a descriptive qualitative approach involving two Group B teachers as research participants. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings showed that teacher creativity in modifying theme-based songs could be identified through three dimensions of creativity, namely fluency, flexibility, and elaboration. Fluency was reflected in the teachers’ ability to generate various ideas for adapting song lyrics to different learning themes. Flexibility was demonstrated through the ability to adjust songs according to classroom situations, learning conditions, and children’s developmental needs. Elaboration was evident in the teachers’ ability to enrich songs through lyric modification and the addition of simple movements that supported learning activities. These findings indicate that theme-based song modification can be utilized as an effective learning strategy to promote active, enjoyable, and meaningful learning experiences for young children